اشتراك التواصل الاجتماعي في اللغة العربية على وجهة النظر التعرض للوسائط لدى طلاب قسم تعليم اللغة العربية بجامعة مولانا مالك إبراهيم الإسلامية الحكومية مالانج - Maryam, Shovi (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
This research aimed to describe the types of social media in the Arabic language that students of Arabic Language Education Department at Maulana Malik Ibrahim State Islamic University Malang subscribed to, and to describe measurement and engagement of the subscription to social media channels or accounts in the Arabic language among students of Maulana Malik Ibrahim State Islamic University Malang. This research was considered quantitative descriptive research. Data collection used interviews and questionnaires. A random sampling sample was chosen of 23 students who participated in an Arabic lesson by taking advantage of social media. The results of this research showed that most of the students in Arabic Language Education Department at Maulana Malik Ibrahim State Islamic University Malang were not accustomed to subscribing to social media in Arabic and accessing it. In Arabic learning, using social media is useful for shaping language environment as   support the improvement of Arabic language skills. Every student can benefit from social media to learn the Arabic language on their own.